The meaning of “Being Art”: Perception and reality - Vazquez, María Laura (2024)
Art and Science try to explore what we consider true. It does not depend on how reality is really, but actually on how we perceive it as humans. So, we create our own reality as we go through space basically. Our body is a good indicator. Art by all means, is the ability of the Being to investigate and create an intimate relationship with itself. Every action in life is art if it leads us to contemplate life with renewed eyes, and to perceive its incessant intelligent flow that blooms from our inner beauty. How many colors are there in our emotions towards reality perception? While contemplating reality, what kind of thoughts are we generating? Do they affect our state of consciousness?